DIGITAL DISCOURSE: LANGUAGE USE IN SOCIAL MEDIA (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article explores the phenomenon of digital discourse and the use of language on social media platforms. Social media has transformed communication practices, shaping how people write, interact, and create meaning online. The study examines linguistic features, including abbreviations, emojis, hashtags, code-switching, and stylistic variations, as well as their sociolinguistic and pragmatic functions. The article also highlights the role of digital discourse in identity construction, community formation, and interpersonal communication. Furthermore, it discusses the implications of social media language for language teaching, literacy development, and digital communication competence. The study emphasizes both the opportunities and challenges presented by social media, including its impact on literacy, language evolution, and cross-cultural communication.